PENYESUAIAN BUDAYA DALAM PERNIKAHAN BEDA AGAMA: STUDI KASUS TENTANG INTERAKSI DAN KONFLIK BUDAYA DI LINGKUNGAN KRATEGIES IN INTERRELIGIOUS MARRIAGE: A CASE STUDY OF CULTURAL INTERACTION AND CONFLICT IN THE FAMILY ENVIRONMENT - Muhammad Husni Abdulah Pakarti; Diana Farid; Iffah Fathiah; Hendriana Hendriana (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2023)
This paper examines cultural adjustment strategies in interfaith marriages within the family environment. Interfaith marriages often present complex cultural challenges, as partners must adapt to different beliefs, traditions, and values ​​that may conflict. This study aims to analyze the cultural adjustment strategies carried out by couples in interfaith marriages, with a focus on cultural interactions and conflicts that arise in the family environment. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with couples who have different religious backgrounds and have been married for at least 5 years. Data analysis was carried out through coding and thematic processes. The results of the study show that couples in interfaith marriages adopt various cultural adjustment strategies to overcome cultural interactions and conflicts in the family environment. These strategies include compromise, mutual understanding, open communication, and respect for differences. Couples are also looking for creative solutions to facilitate family harmony, such as incorporating traditions from both religions in family celebrations. In addition, this research also provides valuable insights for family welfare professionals and marriage counselors in helping couples in interfaith marriages deal with emerging cultural challenges.